Squid suckerin-spider silk fusion protein hydrogel for secretome delivery to chronic wounds - Koh, Kenrick Yee Hong (Nanyang Technological University, 2023)
Chronic wounds are non-healing wounds characterized by a prolonged inflammation phase. Excessive inflammation leads to elevated protease levels and consequently to a decrease in growth factors at wound sites. Stem cell secretome therapy has been identified as a treatment strategy to modulate the microenvironment of chronic wounds via supplementation with anti-inflammatory/growth factors. However, there is a need to develop better secretome delivery systems that are able to encapsulate the secretome without denaturation, deliver the secretome in a sustained manner and that are fully biocompatible. To address this gap, a recombinant squid suckerin-spider silk fusion protein with cell-adhesion motifs capable of thermal gelation at physiological temperatures for encapsulation and subsequent release of the stem cell secretome was developed. Freeze–thaw treatment of the protein hydrogel resulted in a modified porous cryogel that did not elicit fibrotic capsule formation. Proteomics analysis and in vitro wound healing assays demonstrate the potential of the secretome as a wound healing therapeutic. The cryogel is capable of encapsulating the secretome and demonstrated slow degradation and sustained secretome release. Chronic wounds of diabetic mice treated with the secretome-laden cryogel displayed enhanced wound closure, reduced inflammation, increased presence of endothelial cells, increased granulation wound tissue thickness, and a lack of fibrotic scar formation. Overall, these in vivo indicators of wound healing demonstrate that the fusion protein hydrogel displays remarkable potential as a delivery system for secretome-assisted chronic wound healing.